2022
DOI: 10.21203/rs.3.rs-1708936/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysing the Efficiency of National and Sub-national health systems - A Systematic Review of Literature

Abstract: Introduction Health system efficiency is a priority concern for policy makers globally as countries aim to achieve universal health coverage. Efficiency analysis in the health sector has typically focused on the efficiency of healthcare facilities (hospitals, primary healthcare facilities), with few studies focusing on system level (national or sub-national) efficiency. We carried out a thematic review of literature that assessed the efficiency of health systems at the national and sub-national level. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…To identify ways of improving efficiency and hence realize efficiency gains within the Kenyan health system, the Kenya Efficiency Study sought to examine the technical efficiency of the 47 county health systems and the determinants of technical efficiency within the counties. The first phase of the study aimed at developing a model for conceptualizing efficiency and potential determinants of efficiency in Kenya through an extensive literature review [12] as well as a stakeholder's engagement forum [13]. In the first phase, the literature review found that national and sub-national health systems that had inadequate numbers of health workers were less efficient [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify ways of improving efficiency and hence realize efficiency gains within the Kenyan health system, the Kenya Efficiency Study sought to examine the technical efficiency of the 47 county health systems and the determinants of technical efficiency within the counties. The first phase of the study aimed at developing a model for conceptualizing efficiency and potential determinants of efficiency in Kenya through an extensive literature review [12] as well as a stakeholder's engagement forum [13]. In the first phase, the literature review found that national and sub-national health systems that had inadequate numbers of health workers were less efficient [12].…”
Section: Introductionmentioning
confidence: 99%
“…The first phase of the study aimed at developing a model for conceptualizing efficiency and potential determinants of efficiency in Kenya through an extensive literature review [12] as well as a stakeholder's engagement forum [13]. In the first phase, the literature review found that national and sub-national health systems that had inadequate numbers of health workers were less efficient [12]. Further, stakeholders in the Kenyan health system identified human resources for health (HRH) as a potential determinant of health system efficiency at the county level [13].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, this work highlights the potential contribution of qualitative research in assessing the efficiency of health systems. Efficiency analysis in healthcare is dominated by quantitative analysis using frontier approaches (data envelopment analysis and stochastic frontier analysis) [59]. A literature review carried out by Mbau et al (2021) found that only 3% and 2% of studies that assessed the efficiency of national or sub-national health systems used qualitative or mixed methods approaches, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The study is part of a larger study that assessed the level and determinants of health system efficiency at the county level in Kenya. In the first phase of the study, a systematic literature review 13 and stakeholder engagement 14 were conducted that reported PFM processes as key determinants of health system efficiency globally and at the county level in Kenya, respectively. In the second phase, a quantitative assessment of county level health system efficiency and its determinants identified PFM as one of the key determinants of county level efficiency in Kenya 15 .…”
Section: Introductionmentioning
confidence: 99%